Visualization of the tensile fracture behaviors at adhesive interfaces between brass and sulfur-containing rubber studied by transmission electron microscopy. (24th October 2019) - Shimizu, Katsunori; Miyata, Tomohiro; Nagao, Tomohiko; Kumagai, Akemi; Jinnai, Hiroshi
Abstract: Composites of polymers and inorganic materials have recently attracted considerable attention as lightweight tough materials. In this study, we examined the structures and fracture paths at the adhesive interfaces between a sulfur-containing rubber compound and brass formed during vulcanization. Samples consisting of brass fillers dispersed in a rubber matrix were subjected to in situ tensile observations using transmission electron microscopy. Upon uniaxial stretching, fracture occurred between the rubber compound and outermost Cu x S layers of the adhesive interface. With prolonged vulcanization, the adhesive interface became broader and depletion regions of Cu and Zn appeared inside the particles, indicating sample degradation, owing to outward diffusion of the metal elements into the rubber compound. Fracture of the degraded rubber composite occurred along the depletion regions. These observations demonstrate that the adhesiveness of brass and rubber composites strongly depends on the interfacial structures. Graphical abstract: Image 1 Highlights: Fracture and degradation mechanisms of brass–rubber interfaces were studied. Cu and Zn diffused outward from the brass to form Cu x S and ZnS at the brass surface. Depletion regions of Cu and Zn appeared in the inorganic layers. A short vulcanization time led to fracture at the solid layer–rubber interface. Prolonged vulcanization led to fracture along the depletion regions.